(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article examines the measures taken by the President of Uzbekistan Shavkat Mirziyoyev to reduce poverty in the country. Key initiatives such as the Uzbekistan 2030 strategy, economic and social reforms, infrastructure improvements and revision of migration policy are described. Particular attention is paid to successful examples of international experience and their application in Uzbekistan. The results of already implemented measures are analyzed and further steps are proposed to achieve sustainable economic growth and improve the standard of living of the population.